Oḍiśāra parbaparbāṇi, oshābrata, yāniyātrā - Mahanti, Brajamohan; Patnaik, Pathani, 1928- (Utakaḷa Pāṭhaka Saṃsada ānukulyare Oḍiśā Buk Shṭora, 1979)
Articles on the festivals and votive rites (bratas) of Orissa.